SKILL DEVELOPMENT AND WOMEN EMPOWERMENT: ASSESSING THE EFFECTIVENESS OF VOCATIONAL TRAINING CENTERS AND WOMEN LITERACY CENTERS BY TATA POWER DDL - Kumar, Vikramendra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research assesses the impact of Tata Power DDL’s CSR programs for women employment through vocational training centers and women literacy centers. The study is based on an ethnographic survey of 12 districts in North and North-West Delhi. The data was collected by questionnaires, interviews and participant observation with the help of purposive and stratified random sampling techniques. The studies show that rendering vocational training and opening the literacy centers has led positive changes in the women economic and social statuses and played a role in enhancing skills, employment, and literacy levels among the women. However the following challenges were noted; poor infrastructure, low participation in some areas, and lack of resources. These CSR initiatives are very important in the transformation of women’s self-reliance hence the need for the expansion of the programs and enhancement of the current implementation. Further, the study highlights the need to have policy intervention to deal with existing barriers to enhance the participation and achieve sustainable results.